Contrasting seasonal variations of geochemistry and microbial community in two adjacent acid mine drainage lakes in Anhui Province, China. (1st January 2021) - Xin, Ruirui; Banda, Joseph Frazer; Hao, Chunbo; Dong, Huiyuan; Pei, Lixin; Guo, Dongyi; Wei, Pengfei; Du, Zerui; Zhang, Yi; Dong, Hailiang
Abstract: Acid mine drainage (AMD) is generated by the bio-oxidation of sulfide minerals. To understand the AMD formation and evolution, it is necessary to determine the composition and variation of acidophilic community, and their role in AMD ecosystem. In this study, we compared seasonal variations of geochemistry and microbial composition of two adjacent AMD lakes with different formation histories in Anhui Province, China. Lake Paitu (PT) formed in 1970s near a mine dump and the pH was in the range of 3.01–3.16, with the lowest in spring and summer while the highest in winter. The main ions in PT were Al and SO4 2−, whereas Fe concentration was relatively low. The concentrations of these ions were the lowest in summer and the highest in winter. Lake Tafang (TF) formed in around 2013 in a pit was more acidic (pH 2.43–2.75), but the seasonal variation of pH was the same as PT. Compared with Lake PT, TF had higher Fe, lower Al and SO4 2− concentrations, and showed no significant seasonal changes. Despite salient seasonal variations of prokaryotic composition in Lake PT, Ferrovum was the major iron-oxidizing bacterium in most seasons. Furthermore, Lake PT was also rich in heterotrophic bacteria (48.6 ± 15.9%). Both prokaryotic diversity and evenness of Lake TF were lower than PT, and chemolithotrophic iron-oxidizing bacteria (71.7 ± 25.4%) were dominant in almost all samples. Besides Ferrovum, more acid tolerant iron-oxidizer Leptospirillum and Acidithiobacillus were also abundant in Lake TF. Chlamydomonas was the major eukaryote in Lake PT and it flourished repeatedly at the end of December, causing an extremely high chlorophyll a concentration (587 μg/L) at one sampling site in 2016, which provided rich nutrients for heterotrophic bacteria. The main alga in Lake TF was Chrysonebula, but its concentration was low, apparently because of the strong acidity and dark red color of lake water. Graphical abstract: Image 1 Highlights: The pH of Lake Paitu (PT) formed near a mine dump was in the range of 3.01–3.16. The adjacent Lake Tafang (TF) formed in a pit was more acidic (pH 2.43–2.75). Both prokaryotic diversity and evenness of Lake TF were lower than Lake PT. Lake PT was rich in heterotrophs while chemolithotrophs were dominant in Lake TF. Chlamydomonas, the major eukaryote in Lake PT, flourished repeatedly in winter. Abstract : Contrasting seasonal variations of geochemistry and microbial composition of two adjacent AMD lakes with different formation histories were compared.